The impact of a man-made disaster on consumer credit outcomes: Evidence from the 2018 Merrimack Valley natural gas explosions - Bo Zhao (Federal Reserve Bank of Boston, 2023)
This paper is the first to empirically examine the impact of a man-made disaster on consumer credit outcomes. It uses the 2018 Merrimack Valley natural gas explosions as a quasi-random natural experiment and shows that the explosions had a temporary negative effect on debt balances, credit limits, and the number of delinquencies, and did not affect credit scores. The decreases in debt balances and credit limits were likely driven by a decline in credit demand when the affected individuals faced severe life disruption, great uncertainty, and negative financial shocks associated with the disaster. It took some time for the explosions to have an impact on delinquencies, suggesting that the affected individuals may have received short-term forbearance or used default as a last resort. The lack of large, long-lasting effects of the explosions likely reflects the critical role that external assistance to the affected communities played in mitigating the disaster's impact.
Keywords: D14; G51; Q59; 330; Man-made disasters; household credit; consumer debt